'Let the freak-fly fly': Somatic approaches to undoing traditional power dynamics in dance-making. (1st June 2017) - Hamp, Amanda
Miguel Gutierrez, Stephanie Skura and The Architects serve as case studies of dance artists whose somatically informed performance work and creative practices purposefully redistribute power in their creative and dance-making processes. This article analyses their practices in order to consider how they privilege dancers' somatic intelligences and grant dancers authority in creative decision-making. Dancers who practice with Gutierrez, Skura and The Architects rehearse distinct modes of creative authority, which I discus in terms of vital participation, radical permission and contemplative self-government. Such practices can create emancipatory effects for the dancers as social subjects, and reverberate in the sociopolitical world.